The Violence of Looking: An Ethical Critique of Wartime ‘Comfort Women’ Photographs - Philip Charrier (International Journal of Korean History)
This article argues for the removal of wartime ‘comfort women’ photographs and film footage from public circulation in academic, journalistic, museum, and digital contexts due to their potential to cause harm. It focuses specifically on imagery taken without consent during the Second World War, including depictions of both the living and the deceased, which risk exposing or retraumatizing victims and their descendants. While such photographs hold historical significance as evidence of the forced sexual labor system operated by the Japanese military, their continued use as illustrative or evidentiary tools risks perpetuating the structures of violence and degradation that victimized the women. Instead, carefully considered verbal descriptions, combined with survivor testimonies and contextualized historical evidence, can fulfill evidentiary and educational needs without compromising human dignity. By prioritizing survivor narratives over exploitative imagery, this approach respects the agency of those who testified while honoring the intentional silence of those who chose not to disclose their pasts.